The moon in close-up a next generation astronomer's guide - Wilkinson, John.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2010)
Information collected by recent space probes sent to explore the Moon by the USA, the European Space Agency, Japan, China and India has changed our knowledge and understanding of the Moon, particularly its geology, since the Apollo missions. This book presents those findings in a way that will be welcomed by amateur astronomers, students, educators and anyone interested in the Moon. Enhanced by many colour photos, it combines newly acquired scientific understanding with detailed descriptions and labelled photographic maps of the lunar surface. Guided by observation methods explained in the book and 17 Study Areas presented and carefully explained in the last chapter, amateur astronomers can observe these features from Earth using telescopes and binoculars. Readers who consult the photographic maps will gain a better understanding about the Moon?s topography and geology. The book is rounded out by a helpful glossary.
Introducing the Moon -- Probing the Moon -- Geological history of the Moon -- Occultations and eclipses -- Observing the Moon -- Studying the Moon: Study Area 1 ? Mare Crisium -- Study Area 2 ? South east limb -- Study Area 3 ? North east limb -- Study Area 4 ? Mare Tranquillitatis -- Study Area 5 ? Mare Serenitatis -- Study Area 6 ? Mare Nectaris west -- Study Area 7 ? Mare Vaporum -- Study Area 8 ? Central Highlands -- Study Area 9 ? Mare Nubium -- Study Area 10 ? Northern Plains -- Study Area 11 ? Southern Highlands -- Study Area 12 ? Mare Cognitum -- Study Area 13 ? Sinus Iridum -- Study Area 14 ? Mare Insularum -- Study Area 15 ? Mare Humorum -- Study Area 16 ? Oceanus Procellarum -- Study Area 17 ? Western limb -- Glossary.
Electronic reproduction.
Keywords: Electronic books; Moon; Moon -- Observations